Analisis Kebutuhan Media Pembelajaran Digital untuk Mendukung Keterlibatan Belajar Siswa SMP: (Analysis of Digital Learning Media Needs to Enhance Learning Engagement among Junior High School Students) - Anggraini , Siska Dwi; Murtini, Iin (BIODIK, 2026)
Science learning, especially Biology in junior high schools, requires learning media that can help students understand abstract concepts and increase their engagement in the learning process. However, the use of learning media in schools is still less varied and does not fully meet student needs. Therefore, this study aims to analyze the need for digital learning media to support learning engagement of junior high school students. This study used a mixed methods approach with a concurrent triangulation design. The research subjects consisted of 32 seventh-grade students of UPT SMP Negeri 4 Tuban and one science teacher. Data collection was carried out through a learning media needs questionnaire and interview guidelines that had been validated through expert judgment by a Biology Education lecturer. Quantitative data were analyzed descriptively using percentages, while qualitative data were analyzed using the Miles and Huberman model. The results showed that the need for learning media was in the percentage range of 74.9%–82.2%, with the majority of aspects being in the high category. The aspect of media type preference obtained the highest percentage at 82.2%, while the aspect of media utilization and availability by teachers obtained the lowest percentage at 74.9%. These findings indicate that students need varied, engaging digital learning media that are technology- and innovation-based. Therefore, it is necessary to develop and optimize learning media that are tailored to student needs and school learning conditions. Abstrak. Penelitian ini bertujuan untuk mengidentifikasi kebutuhan media pembelajaran dalam mendukung proses belajar siswa SMP. Penelitian menggunakan pendekatan mixed methods dengan subjek penelitian yaitu siswa kelas VII H UPT SMP Negeri 4 Tuban yang berjumlah 32 siswa serta satu orang guru IPA. Pengumpulan data dilakukan melalui angket kebutuhan media pembelajaran dengan skala Likert dan wawancara dengan guru IPA. Data kuantitatif dianalisis secara deskriptif menggunakan persentase, sedangkan data kualitatif dianalisis dengan model Miles dan Huberman yang terdiri dari proses tahapan analisis data yang mencakup reduksi, penyajian, dan interpretasi hasil. Hasil analisis menunjukkan bahwa kebutuhan media pembelajaran berada pada rentang persentase 74,9% hingga 82,2%. Aspek preferensi jenis media yang digunakan memperoleh persentase tertinggi sebesar 82,2%, sedangkan aspek pemanfaatan dan ketersediaan media oleh guru memperoleh persentase terendah sebesar 74,9%. Berdasarkan kategori tingkat kebutuhan, mayoritas aspek berada pada kategori tinggi. Temuan ini menunjukkan bahwa media pembelajaran sangat dibutuhkan untuk mendukung proses pembelajaran siswa SMP, khususnya media yang bervariasi serta berbasis teknologi dan inovasi. Oleh sebab itu, diperlukan pengembangan dan optimalisasi media pembelajaran yang sesuai dengan kebutuhan siswa dan kondisi pembelajaran di sekolah.